Results 1 to 2 of 2

Math Help - Proving by Induction

  1. #1
    Junior Member
    Joined
    Nov 2008
    Posts
    66

    Proving by Induction

    Hey guys! I need some help with this problem

    Consider the sequence defined by

    an = 8an−1 − 12an−2 + 3n for n ≥ 2 and a0 = 0, a1 = 1

    Prove by induction on n that an = 6^n + 2^(n+1) − 3^(n+1) is a solution to this recurrence.
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Junior Member
    Joined
    Nov 2012
    From
    NY
    Posts
    62
    Thanks
    8

    Re: Proving by Induction

    an = 6^n + 2^(n+1) − 3^(n+1) doesn't appear to be a valid solution. Check for n = 2. According to the recurrence: a2 = 8a1 - 12a0 + 3*2 = 8 - 0 + 6 = 14. Substituting n = 2 in the purported solution gives a2 = 6^2 + 2^3 - 3^3 = 36 + 8 - 27 = 17.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Proving by induction
    Posted in the Advanced Math Topics Forum
    Replies: 1
    Last Post: November 17th 2012, 02:42 PM
  2. Proving by induction
    Posted in the Algebra Forum
    Replies: 7
    Last Post: September 23rd 2012, 10:16 PM
  3. Proving Complete Induction
    Posted in the Discrete Math Forum
    Replies: 3
    Last Post: June 10th 2011, 01:13 PM
  4. proving (by induction)
    Posted in the Discrete Math Forum
    Replies: 1
    Last Post: August 30th 2009, 04:50 PM
  5. Need help proving!! Mathematical Induction
    Posted in the Discrete Math Forum
    Replies: 1
    Last Post: October 15th 2008, 06:38 PM

Search Tags


/mathhelpforum @mathhelpforum